(untitled) (TUTA Journal, 2022)
2’-hydroxy chalcone imines (IIIA-T) on refluxing in DMSO for 2 hours in presence of catalytic amount of iodine in presence of conc. H2SO4, afford the corresponding aminoflavone (IVA-T) in high yield. This method is quicker and appears to be of general applicability. The structures were established on the basis of spectral data (IR, NMR) and chemical reactions.